ANALYSIS AND EXPERIMENTAL VERIFICATION OF THE EFFECТ OF ASSEMBLY STRESS ON THE RANDOM FATIGUE LIFE OF AIRCRAFT PIPELINE - ZHAO XuSheng; CHEN Guo; ZHANG Xu; QIAN Jin (Jixie qiangdu)
Aiming at the fatigue fracture problem of aireraft hydraulic pipeline connector, the fatigue life of hydraulic conduit with axial assembly deviation was predicted based on random vibration theory. Starting with the establishment of the finite element model of the pipeline connector of the real aircraft hydraulic system, the influence law of the assembly stress caused by the axial assembly deviation on the structure was analyzed, and the damping ratio of the pipeline connector under different axial deviation is obtained through the test. The random vibration analysis was carried out by using the finite element analysis software, and the stress response power spectral density function of the dangerous part was obtained. Combined with Miner linear damage theory, the random vibration fatigue life of the pipeline connector with assembly stress was predicted. The resonance fatigue test of pipeline was designed and carried out. It is found that the crack initiation position and the decreasing trend of fatigue life of pipeline are consistent with the simulation results. The simulation and test results show that when the axial deviation reaches 0.8 mm, it seriously affects the flight safety. The research results provide theoretical reference and technical support for the design and assembly theory of aviation hydraulic pipeline.